Pengaruh Sistem Pencatatan Barang terhadap Kinerja Gudang pada PT. Hunter Douglas Indonesia di Cikarang - Miskul Firdaus; Faisal Adam Ar Rasyid; Simon Gultom (Institut Transportasi dan Logistik Trisakti, 2018)
PT. Hunter Douglas Indonesia is a foreign interior manufacture company that produces modern curtains/window covering and architectural products. The purpose of this study is to find out the effect of the stock opname system to warehouse performance of the company in Cikarang. The method used in this study was field and library research. The study used simple linear regression, coefficient correlation, coefficient determination, and hypothesis testing to analyse the data. The result shows that t-count (5,459) is more than t-table (1,701) which means that there is a significant correlation between neat stock opname system and the warehouse performance in the company. It is proven that the hyphothesis is correct.PT. Hunter Douglas Indonesia is a foreign interior manufacture company that producesmodern curtains/window covering and architectural products. The purpose of this study is tofind out the effect of the stock opname system to warehouse performance of the company inCikarang. The method used in this study was field and library research. The study usedsimple linear regression, coefficient correlation, coefficient determination, and hypothesistesting to analyse the data. The result shows that t-count (5,459) is more than t-table (1,701)which means that there is a significant correlation between neat stock opname system andthe warehouse performance in the company. It is proven that the hyphothesis is correct.